PERSEPSI MASYARAKAT KELURAHAN KASAWARI KECAMATAN AERTEMBAGA KOTA BITUNG PROVINSI SULAWESI UTARA TERHADAP KEBIJAKAN PENGELOLAAN TAMAN WISATA ALAM BATUANGUS - Yusuf L. Tamarol; Reynold P. Kainde; Semuel P. Ratag (COCOS, 2015)
ABSTRACT  Has conducted research that aims to describe the Kasawari community perception of the policy management of Batuangus Nature and Tourism Park. Research conducted at the Kasawari Village, Aertembaga District, Bitung City, Province of North Sulawesi. Research conducted by interview using the questionnaire at 73 respondents, and then grouped the data obtained, interpreted and studied descriptively. Results of the study is that Kasawari people know of the existence of  Batuangus Nature and Tourism Park but perceive it as a protected forest that has not been beneficial. Communities know that there is a regulation and legislation and community forestry agree with the prohibitions and sanctions contained therein. Public perception related to the preservation of Batuangus Nature and Tourism Park tends to favor the management policy. Public perception of community empowerment as an activity that is positive but need to consider the types of assistance that can support the majority of community work. In addition, the public perceives well too for extension activities. The Identity of management institutions not so well known by the public, according to the public perception that all of government agencies on duty in the forestry sector is the manager of Batuangus Nature and Tourism Park. There are two (2) main hope related people management policies Batuangus Nature Park namely the availability of water and the positive impact of the optimization function of Batuangus Nature and Tourism Park.    Keywords : perception, policy, Batuangus NTP